Preoperative Meniscus: Pitfalls and Traps to Avoid - Yoo, Hye Jin; Ryu, Kyung Nam; Park, Ji Seon; Jin, Wook; Park, So Young; Kang, Hye Jin; Kim, Hyun Soo; Kwon, Gene Hyuk (Taehan Yŏngsang Ŭihakhoe chi, 2022)
To accurately interpret knee MRI, it is important not only to know the basic meniscal anatomy but also to distinguish it from that under pathological conditions. Thus, it would be helpful to know the normal meniscus variants (false positives) that could be mistaken for meniscal tears, and tears that could easily be missed and incorrectly diagnosed as normal (false negatives). False positives include synovial recesses, meniscal flounce, the relationship between the popliteus tendon and lateral meniscus, transverse ligament, the anterior root of the meniscus, and meniscofemoral ligament. False negatives include focal radial tears, flap tears, posterior root tears, meniscocapsular separation, and discoid meniscal tears. In this pictorial essay, we reviewed the imaging data obtained in the aforementioned cases.